When It Cannot Get Better or Worse: The Asymmetric Impact of Good and Bad News on Bond Returns in Expansions and Recessions - Beber, Alessandro; Brandt, Michael W. (Review of Finance, 2010)
Abstract We examine empirically the response of bond returns and their volatility to good and bad macroeconomic news during expansions and recessions. We find that macroeconomic announcements are most important when they contain bad news for bond returns in expansions and, to a lesser extent, good news in contractions. In expansions, the bond market responds most strongly to bad news in non-farm payrolls, while in recessions good news about inflation is relatively more important. We also document that macroeconomic news impacts the volatility of bond returns at all maturities by increasing jump intensities and altering the jump size distribution.